Exploring the Diversity in Oil Content, Fatty Acid Profiles, and Seed Coat Color in Sudanese Sesame Germplasm: Implications for Breeding and Crop Improvement - Mohammed Elsafy; Wafa Badawi; Ali Zakaria; Tilal Sayed Abdelhalim; Mahbubjon Rahmatov; Eva Johansson (Plant-Environment Interactions)
ABSTRACT Sesame, a key oilseed crop, thrives in arid environments and offers high‐quality oils. Sudan, a major producer and center of sesame genetic diversity, remains underutilized in breeding efforts. This study analyzed 87 Sudanese sesame accessions, revealing significant variations in oil content, fatty acid composition, and seed coat color. The findings highlight the potential of Sudanese germplasm for improving oil quality and broadening trait diversity in breeding programs. Oil content ranged from 32.8% to 50.2%, with oleic acid (41.3%–47.6%) and linoleic acid (35.0%–41.4%) as the predominant fatty acids, consistent with other regions. Some samples showed exceptionally high oleic acid levels. Seed coat color varied significantly, particularly in lightness (L*), but it showed no correlation with oil content or fatty acid composition. Its potential link to bioactive compounds warrants further study. Principal coordinates analysis showed no link between oil levels, fatty acid profiles, and the original collection sites. The findings highlight the breeding potential of Sudanese sesame germplasm, particularly for developing varieties with high unsaturated fatty acids, such as oleic acid, and diverse seed coat colors. Further studies across environments and genetic investigations are needed to ensure trait stability and optimize their use.